Repeated oral glucose tolerance tests in women at risk for gestational diabetes mellitus. (November 2019) - de Wit, L.; Bos, D.M.; van Rossum, A.P.; van Rijn, B.B.; Boers, K.E.
Abstract: Objective: Pregnant women with a negative oral glucose tolerance test (OGTT) between 24–28 weeks as part of risk-based screening for gestational diabetes mellitus (GDM) may develop clinical signs or symptoms suggestive for GDM in the third trimester. We aimed to determine the additional yield of repeating an OGTT to detect missed GDM in this group and assess patient characteristics and indications associated with a positive second OGTT. Study design: We conducted a retrospective cohort study of women with a negative OGTT between 24–28 weeks of pregnancy in two hospitals in the Netherlands. Patient characteristics, pregnancy outcomes, OGTT results and indications were compared between women with normal (non-GDM) and abnormal (GDM) results of the second OGTT, using the WHO 1999 criteria (fasting glucose ≥7.0 mmol/L or 2 -h post load ≥7.8 mmol/L). We used receiver operating characteristic (ROC) curve analysis to determine cut-offs for fasting and 2 -h glucose values of the index OGTT that were associated with a positive OGTT in the third trimester. Results: Of 3147 women at risk for GDM, 183 underwent a second OGTT in the third trimester following their regular OGTT at 24–28 weeks. In 43 women (23.5%) GDM was diagnosed based on the second OGTT. A history of GDM was associated with subsequent GDM diagnosis, with an odds ratio of 2.6 (95% CI 1.0–6.3). Both fasting and 2 -h post load glucose values of the index OGTT were significantly higher in women with abnormal OGTT results later in pregnancy. Index OGTT glucose value cut-offs of 4.8 mmol/L (fasting) and 6.5 mmol/L (2 -h) had positive predictive values of 0.32 and 0.47 for a positive OGTT in the third trimester, and negative predictive values of 0.83 and 0.90, respectively. Fetal growth as a clinical symptom for GDM was the most frequent indication for repeating the OGTT, resulting in the diagnosis of GDM in 22.7% of women tested for this indication. Conclusion: Repeating an OGTT after initial negative screening results in additional GDM diagnoses. In case of clinical signs, especially in women with additional risk factors such as a history of GDM or higher index OGTT glucose values, repeating an OGTT could be considered.